KALIGRAFI DAN PENERAPANNYA DALAM SENI DESIGN INTERIROR MASJID QUBA MADINAH - Ruwiyah Zamzam; Balqis Ufairo (Jurnal Ekshis, 2024)
The journal describes the types of calligraphy strokes and the application of calligraphy art in the field of interior design. Calligraphy is an art that contains aesthetic and spiritual values ​​in it, while interior design is a series of planning processes for a space facility in accordance with the needs of its users physically and psychologically in order to give the feel of a comfortable space for its users. This study uses a qualitative method of content analysis as the main approach with a descriptive approach as an additional approach. This study aims to describe what is sulus calligraphy and how to apply it in the interior design of the Cuban mosque in the city of Medina, the result is that the interior design space using sulus type Arabic calligraphy when combined with the spiritual dimension in the overall composition of the interior design is able to perfect the meaning and aesthetic value of the art of calligraphy